Adopting Delayed Cord Clamping in Neonates who Cry/Breathe at Birth: A Quality Improvement Project at a Tertiary Care Hospital in Bengaluru, Karnataka, India - R Gowtham; MG Suman; Megha Varsha Madhusudan; V Sandhya (Indian Journal of Neonatal Medicine and Research)
Introduction: Delayed Cord Clamping (DCC) involves waiting to clamp the umbilical cord for a duration of usually 60 seconds to three minutes following the baby’s birth. This practice has garnered increasing attention due to its potential to significantly improve neonatal outcomes. Aim: To increase DCC rates at study Institute, by about 80% in neonates who breathe and cry at birth. Materials and Methods: This Quality Improvement (QI) study was carried out in the Department of Paediatrics at Dr. BR Ambedkar Medical College and Hospital in Bengaluru, Karnataka, India, from 1st September 2023 to 15th October 2023 (a period of 6 weeks). This project was planned and conducted with a multidisciplinary team and aimed to increase DCC rates among deliveries conducted (fitting the inclusion criteria) in the Institute, abiding by the World Health Organisation (WHO) protocol. Results: This QI project increased rates of DCC with each Plan-Do-Study-Act cycle (PDSA), ultimately meeting the aim over six weeks, increasing from zero to 87.87%. Conclusion: Simple and inexpensive interventions, such as providing education, repetitive reinforcement and collaborative teamwork with minimal resources, quickly led to improvements in DCC rates. DCC presents significant benefits for neonatal health, particularly in improving iron status and supporting cardiovascular and respiratory transitions.